Pelatihan Pengenalan Autocad 2D Bagi Siswa Di SMA Kesatrian 2 Yayasan Pendidikan Kesatrian Semarang - Seno Suharyo; Trias Widorini; Wardana Galih Pamungkas (Universitas Semarang, 2023)
The rapid development of technology today makes people adapt. In the field of education, especially in the field of engineering drawing design, several computer programs have been very helpful in completing work with good results. Human resources are needed who are willing to learn and able to adapt to technological advances so that they can run computer programs optimally. For high school students who are interested in continuing their education in engineering at the university, skills in using computer programs will be very helpful. Therefore, the Civil Engineering Department, Faculty of Engineering, University of Semarang carries out community service, especially for students of SMA Kesatrian 2 Semarang, namely